Modeling and simulation of meteor burst channel - Bing XIA; Linlin LI; Yanshan ZHENG (Dianxin kexue)
In the test of the actual performance of communication device and software based on meteor burst,a model of meteor burst communication channel was established to solve the complexity of channel and difficulty of measurement.By analyzing the mathematic models of meteor burst channel,single underdense meteor trail channel and single overdense meteor trial channel were modeled as basis.Underdense meteor cluster and multipath channel were proposed to built a hybrid model based on probability principles.Combining with meteor arrival interval model,the simulation of meteor burst channel was realized by C++ programming tool.The simulation result can provide underdense meteor trail,overdense meteor trial,underdense meteor cluster and multipath channel.It indicates that the characteristics of the meteor burst channel model are basically matched with those of real channel.The result verifies usability and justifiability of the model.